A retrospective cohort study on the association between elevated preoperative red cell distribution width and all-cause mortality after noncardiac surgery. (June 2020) - Olafsson, Halldor B.; Sigurdarson, Gissur A.; Christopher, Kenneth B.; Karason, Sigurbergur; Sigurdsson, Gisli H.; Sigurdsson, Martin I.
Abstract: Background: Elevated red cell distribution width (RDW) has been associated with worse outcomes in several medical patient populations. The aim of this study was to investigate the association of increased preoperative RDW and short- and long-term mortality after noncardiac surgery. Methods: This investigation was a retrospective cohort study including all patients undergoing noncardiac surgery between 2005 and 2015 at Landspitali—the National University Hospital in Iceland. Patients were separated into five predefined groups based on preoperative RDW (≤13.3%, 13.4–14.0%, 14.1–14.7%, 14.8–15.8%, and >15.8%). The primary outcome was all-cause long-term mortality and secondary outcomes included 30-day mortality, length of stay, and readmissions within 30 days, compared with propensity score matched (PSM) cohort from patients with RDW ≤13.3%. Results: There was a higher hazard of long-term mortality for patients with RDW between 14.8% and 15.8% (hazard ratio=1.33; 95% confidence interval, 1.15–1.59; P <0.001) and above 15.8% (hazard ratio=1.66; 95% confidence interval, 1.41–1.95; P <0.001), compared with matched controls with RDW ≤13.3%. This association held in multiple patient subgroups. For secondary outcomes, there was no difference in 30-day mortality, length of stay, or risk of readmission within 30 days. Conclusions: Increased preoperative RDW is associated with increased long-term mortality after noncardiac surgery. RDW could be a composite biomarker of pre-existing chronic inflammation and poor nutritional status. Future studies should clarify if this is a modifiable risk factor for improved surgical outcomes. Editor's key points: Increases in the red cell distribution (RDW) are observed in patients with chronic inflammation or poor nutrient status. An RDW increase has been shown to be associated with unfavorable outcome in chronic diseases. This retrospective study investigated the association of preoperative RDW with short- and long-term mortality in patients who underwent noncardiac surgery. Patients with an increased preoperative RDW showed an increased hazard for postoperative long-term mortality. Preoperative RDW should be further investigated as a prognostic marker for outcome in patients undergoing noncardiac surgery.